The untold tales of Armistead Maupin [videorecording (DVD)] - Kroot, Jennifer M.; Maupin, Armistead; Linney, Laura; McKellen, Ian; Dukakis, Olympia; Gaiman, Neil; Cho, Margaret; Tan, Amy; Maupin, Armistead (Wolfe Video, LLC, 2017)
Jennifer Kroot's documentary about the creator of Tales of the City moves nimbly between playful and poignant and laugh-out-loud funny. Maupin offers a disarmingly frank look at the journey that took him from the jungles of Vietnam to the bathhouses of '70's San Francisco to the front line of the American culture war.